2022
DOI: 10.1039/d2cc04383a
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation is regulated by both the stability and topology of G-quadruplex

Abstract: Since DNA methylation alters chromatin state and regulates gene expression, elucidating the regulatory mechanisms of DNA methylation in response to environmental changes in the cell is crucial and urgent in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…DNA methylation involves the covalent attachment of a methyl group to the 5th carbon position of cytosine within CpG dinucleotides in the genome and is catalyzed by DNA methyltransferases [ 13 ]. Extensive research has demonstrated that DNA methylation can induce changes in chromatin structure, DNA conformation, DNA stability, and interactions between DNA and proteins, thereby regulating gene expression [ 14 , 15 ]. DNA methylation is among the earliest discovered and most thoroughly studied epigenetic regulatory mechanisms.…”
Section: Basic Mechanism Of Dna Methylationmentioning
confidence: 99%
“…DNA methylation involves the covalent attachment of a methyl group to the 5th carbon position of cytosine within CpG dinucleotides in the genome and is catalyzed by DNA methyltransferases [ 13 ]. Extensive research has demonstrated that DNA methylation can induce changes in chromatin structure, DNA conformation, DNA stability, and interactions between DNA and proteins, thereby regulating gene expression [ 14 , 15 ]. DNA methylation is among the earliest discovered and most thoroughly studied epigenetic regulatory mechanisms.…”
Section: Basic Mechanism Of Dna Methylationmentioning
confidence: 99%